A bias–variance evaluation framework for information retrieval systems. Issue 1 (January 2022) - Zhang, Peng; Gao, Hui; Hu, Zeting; Yang, Meng; Song, Dawei; Wang, Jun; Hou, Yuexian; Hu, Bin
Abstract: In information retrieval (IR), the improvement of the effectiveness often sacrifices the stability of an IR system. To evaluate the stability, many risk-sensitive metrics have been proposed. Since the theoretical limitations, the current works study the effectiveness and stability separately, and have not explored the effectiveness–stability tradeoff. In this paper, we propose a Bias–Variance Tradeoff Evaluation (BV-Test) framework, based on the bias–variance decomposition of the mean squared error, to measure the overall performance (considering both effectiveness and stability) and the tradeoff between effectiveness and stability of a system. In this framework, we define generalized bias–variance metrics, based on the Cranfield-style experiment set-up where the document collection is fixed (across topics) or the set-up where document collection is a sample (per-topic). Compared with risk-sensitive evaluation methods, our work not only measures the effectiveness–stability tradeoff of a system, but also effectively tracks the source of system instability. Experiments on TREC Ad-hoc track (1993–1999) and Web track (2010–2014) show a clear effectiveness–stability tradeoff across topics and per-topic, and topic grouping and max–min normalization can effectively reduce the bias–variance tradeoff. Experimental results on TREC Session track (2010–2012) also show that the query reformulation and increase of user data are beneficial to both effectiveness and stability simultaneously. Highlights: A unified bias–variance metric evaluates retrieval effectiveness–stability tradeoff. A generalized bias–variance metric is defined based on across topic and per-topic. Studying the factors that influence the bias–variance metric (topic grouping, etc.). Decomposition of a variance can effectively track the source of system instability.